2006
DOI: 10.1002/mc.20164
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of N‐acetyltransferase 1 and 2 catalyzing the N‐acetylation of 4‐aminobiphenyl and O‐acetylation of N‐hydroxy‐4‐aminobiphenyl in the congenic rapid and slow acetylator Syrian hamster

Abstract: N-acetyltransferase 1 (NAT1) and 2 (NAT2) enzymes catalyzing both deactivation (N-acetylation) and activation (O-acetylation) of arylamine carcinogens such as 4-aminobiphenyl (ABP) were investigated in a Syrian hamster model congenic at the NAT2 locus. NAT2 catalytic activities (measured with p-aminobenzoic acid) were significantly (P < 0.001) higher in rapid than slow acetylators in all tissues (except heart and prostate where activity was undetectable in slow acetylators). NAT1 catalytic activities (measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 40 publications
(60 reference statements)
6
36
0
Order By: Relevance
“…N-acetyltransferase activities were measured with the human NAT2-selective substrate sulfamethazine using HPLC to separate N-acetylsulfamethazine product from sulfamethazine substrate as described previously (25). N-hydroxy-MeIQx O-acetyltransferase assays were determined by HPLC using modifications of an assay described recently (26). Briefly, reaction mixtures containing equal amounts of cell lysate protein, 1 mg/mL deoxyguanosine, 100 Amol/L N-hydroxy-MeIQx (Toronto Research Chemicals), and 1 mmol/L acetyl-CoA were incubated at 37jC for 10 min and stopped by the addition of watersaturated ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…N-acetyltransferase activities were measured with the human NAT2-selective substrate sulfamethazine using HPLC to separate N-acetylsulfamethazine product from sulfamethazine substrate as described previously (25). N-hydroxy-MeIQx O-acetyltransferase assays were determined by HPLC using modifications of an assay described recently (26). Briefly, reaction mixtures containing equal amounts of cell lysate protein, 1 mg/mL deoxyguanosine, 100 Amol/L N-hydroxy-MeIQx (Toronto Research Chemicals), and 1 mmol/L acetyl-CoA were incubated at 37jC for 10 min and stopped by the addition of watersaturated ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…Both classes of carcinogens induce prostate tumors in animal models (8,9). Recently, it has been reported that human prostate tissue, as well as prostate cells in culture, contains measurable levels of the enzymes required for the activation of arylamine carcinogens (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…(Testa and Mayer, 2006;Uetrecht and Trager, 2007;Long and Cravatt, 2011;Yang et al, 2011;Bachovchin and Cravatt, 2012;Oda et al, 2015). Additionally, metabolites arising from conjugative enzymes (phase II metabolism), including uridine 59-diphospho-glucuronosyltransferases (UGT) (Tukey and Strassburg, 2000;Oda et al, 2015), N-acetyl transferases (Hein et al, 2006), glutathione S-transferases (Armstrong, 1997;Eaton and Bammler, 1999;Salinas and Wong, 1999;Sheehan et al, 2001), sulfotransferases (Strott, 2002;Riches et al, 2009), and methyltransferases (Petrossian and Clarke, 2011), are also frequently identified.…”
Section: Introductionmentioning
confidence: 99%